Strengthening Community Solidarity and Togetherness through Friendly Activities and Gift Giving on August 17 - Nursalam; Purnamasari, Nur Indah; Firdaus, Muh. Nur Ridho Chaerul (Jurnal Al Maesarah, 2025)
This research aims to analyze the role of friendship activities and giving gifts in strengthening community solidarity and togetherness in Bontoboddia Hamlet, Lempangang Village, Bajeng District, Gowa Regency, in the context of celebrating Independence Day on August 17. Descriptive design. Data was obtained through in-depth interviews, participant observation, and documentation. The research subjects included the activity committee, community leaders, and residents involved in the celebration, namely the Lempangang village community consisting of three hamlets: Bontoboddia, Bontomanai, and Tamalalang hamlets. The research results show that friendship activities contribute greatly to creating positive social interactions between residents, increasing the sense of family, and strengthening the spirit of cooperation. Apart from being a form of appreciation, giving gifts is also a motivation for individuals to be more active in participating in competitions and joint activities. However, this study also found several challenges, such as the lack of involvement of the younger generation and budget constraints, which affected the smooth implementation of activities.